Dopamine D1/D5 Receptors in the Retrosplenial Cortex Are Necessary to Consolidate Object Recognition Memory - de Landeta, Ana Belén; Medina, Jorge H.; Katche, Cynthia (Frontiers in Behavioral Neuroscience, 2022)
The retrosplenial cortex (RSC) has been widely related to spatial and contextual memory. However, we recently demonstrated that the anterior part of the RSC (aRSC) is required for object recognition (OR) memory consolidation. Here, we aimed to analyze the requirement of dopaminergic inputs into the aRSC for OR memory consolidation in male rats. We observed amnesia at 24 h long-term memory when infused SCH23390, a D1/D5 dopamine receptors antagonist, into aRSC immediately after OR training session. However, the same infusion had no effect on OR short-term memory. Then, we analyzed whether the ventral tegmental area (VTA) is necessary for OR consolidation. VTA inactivation by intra-VTA administration of muscimol, a GABAA agonist, immediately after OR training session induced amnesia when animals were tested at 24 h. Moreover, we observed that this VTA inactivation-induced amnesia was reversed by the simultaneous intra-aRSC delivery of SKF38393, a D1/D5 receptors agonist. Altogether, our results suggest that VTA dopaminergic inputs to aRSC play an important modulatory role on OR memory consolidation.